What goes around comes around: How large are spillbacks from US monetary policy? - Max Breitenlechner; Georgios Georgiadis; Ben Schumann (European Central Bank (ECB), 2021)
We quantify spillbacks from US monetary policy based on structural scenario analysis and minimum relative entropy methods applied in a Bayesian proxy structural vector-autoregressive model estimated on data for the time period from 1990 to 2019. We find that spillbacks account for a non-trivial share of the overall slowdown in domestic real activity in response to a contractionary US monetary policy shock. Our analysis suggests that spillbacks materialise as Tobin's q/cash flow and stock market wealth effects impinge on US investment and consumption. Contractionary US monetary policy depresses foreign sales of US firms, which reduces their valuations/cash flows and thereby induces cutbacks in investment. Similarly, as contractionary US monetary policy depresses US and foreign equity prices, the value of US households' portfolios is reduced, which triggers a drop in consumption. Net trade does not contribute to spillbacks because US monetary policy affects exports and imports similarly. Finally, spillbacks materialise through advanced rather than emerging market economies, consistent with their relative importance in US firms' foreign demand and US foreign equity holdings.
Keywords: F42; E52; C50; 330; US monetary policy; spillovers; spillbacks; Bayesian proxy structuralVAR models